Adverse outcomes after percutaneous dilatational tracheostomy versus surgical tracheostomy in intensive care patients: case series and literature review - Jarosz K; Kubisa B; Andrzejewska A; Mrówczyńska K; Hamerlak Z; Bartkowska-Śniatkowska A (Dove Medical Press, 2017)
Konrad Jarosz,1 Bartosz Kubisa,2 Agata Andrzejewska,3 Katarzyna Mrówczyńska,3 Zbigniew Hamerlak,4 Alicja Bartkowska-Śniatkowska5 1Department of Clinical Nursing, Pomeranian Medical University, 2Thoracic Surgery and Transplantation Department, Pomeranian Medical University, 3Anaesthesiology and Intensive Care Department, Pomeranian Medical University, 4Stomatology Department, Pomeranian Medical University, 5Anaesthesiology and Pediatric Intensive Care Department, Poznan University of Medical Sciences, Szczecin, Poland Abstract: Tracheostomy is a routinely done procedure in the setting of intensive care unit (ICU) in patients requiring prolonged mechanical ventilation. There are two ways of making a tracheostomy: an open surgical tracheostomy and percutaneous dilatational tracheostomy. Percutaneous dilatational tracheostomy is associated with fewer complications than open tracheostomy. In this study, we would like to compare both techniques of performing a tracheostomy in ICU patients and to present possible complications, methods of diagnosing and treating and minimizing their risk. Keywords: tracheostomy, percutaneous tracheostomy, percutaneous dilatational tracheostomy, bronchoscopy, surgical tracheostomy, tracheoesophageal fistula, tracheostomy complications